Full waveform inversion of time-lapse VSP data - Egorov, Anton (Curtin University, 2018)
Vertical seismic profile (VSP) is one of the technologies for monitoring hydrocarbon production and CO2 geosequestration. However, quantitative interpretation of time-lapse VSP is challenging due to its irregular distribution of source-receiver offsets. One way to overcome this challenge is to use full waveform inversion (FWI), which does not require regular offsets. We present a workflow of elastic FWI applied to offset vertical seismic profile data for the purpose of identification and estimation of time-lapse changes introduced by injection of 15,000 t of CO2-rich gas mixture at 1.5 km depth. Application of this workflow to both synthetic and field data shows that elastic FWI is able to detect and quantify the time-lapse anomaly in P wave velocity with the magnitude of 100–150 m/s.